The Lifebox Surgical Headlight Project: engineering, testing, and field assessment in a resource‐constrained setting. Issue 13 (27th June 2020) - Starr, N.; Panda, N.; Johansen, E. W.; Forrester, J. A.; Wayessa, E.; Rebollo, D.; August, A.; Fernandez, K.; Bitew, S.; Mammo, T. Negussie; Weiser, T. G.
Abstract : Background: Poor surgical lighting represents a major patient safety issue in low‐income countries. This study evaluated device performance and undertook field assessment of high‐quality headlights in Ethiopia to identify critical attributes that might improve safety and encourage local use. Methods: Following an open call for submissions (December 2018 to January 2019), medical and technical (non‐medical) headlights were identified for controlled specification testing on 14 prespecified parameters related to light quality/intensity, mounting and battery performance, including standardized illuminance measurements over time. The five highest‐performing devices (differential illumination, colour rendering, spot size, mounting and battery duration) were distributed to eight Ethiopian surgeons working in resource‐constrained facilities. Surgeons evaluated the devices in operating rooms, and in a comparative session rated each headlight in terms of performance and willingness to purchase. Results: Of 25 submissions, eight headlights (6 surgical and 2 technical) met the criteria for full specification testing. Scores ranged from 8 to 12 (of 14), with differential performance in lighting, mounting and battery domains. Only two headlights met the illuminance parameters of more than 35 000 lux during initial testing, and no headlight satisfied all minimum specifications. Of the five headlights evaluated in Ethiopia, daily operation logbooks noted variability in surgeons' opinions of lighting quality (6–92 per cent) and spot size (0–92 per cent). Qualitative interviews also yielded important feedback, including preference for easy transport. Surgeons sought high quality with price sensitivity (using out‐of‐pocket funds) and identified the least expensive but high‐functioning device as their first choice. Conclusion: No device satisfied all the predetermined specifications, and large price discrepancies were critical factors leading surgeons' choices. The favoured device is undergoing modification by the manufacturer based on design feedback so an affordable, high‐quality surgical headlight crafted specifically for the needs of resource‐constrained settings can be used to improve surgical safety. Abstract : Poor surgical lighting represents a major patient safety issue in low‐income countries, and currently there is no fit‐for‐purpose surgical headlight to meet the demands of this setting, both in terms of design and price. In this study, engineering testing of 14 surgical headlights, and field testing of five finalist candidate headlights with surgeons in Ethiopia, was undertaken to determine the best performing light and evaluate critical attributes for further design modifications. After testing in operating room working conditions and a head‐to‐head comparison test, one headlight was chosen that best fit design and cost preferences; this headlight will undergo further design modifications and testing to develop a final product for wide distribution and improvement of surgical safety. Bring the light Abstract : Antecedentes: Una iluminación quirúrgica deficiente conlleva importantes problemas de seguridad para los pacientes en países de bajos ingresos. En Etiopía, se evaluó el rendimiento y la capacidad de iluminar el campo quirúrgico de varias lámparas de alta calidad para identificar aspectos esenciales que podrían mejorar la seguridad y fomentar su uso local. Métodos: Tras una convocatoria abierta (diciembre de 2018‐enero de 2019), se identificaron lamparás médicas y técnicas (no médicas) para realizar un análisis de 14 variables previamente definidas en relación con la calidad/intensidad de la luz, montaje y rendimiento de la batería, además de mediciones estandarizadas de iluminancia a largo plazo. Los cinco dispositivos de mayor rendimiento (iluminación diferencial, reproducción del color, tamaño del foco, montaje y duración de la batería) se distribuyeron entre 8 cirujanos etíopes que trabajaban en instalaciones con recursos limitados. Los cirujanos evaluaron los dispositivos en quirófano y en sesiones comparativas calificaron el rendimiento de cada lámpara y la disposición para su compra. Resultados: De las 25 propuestas presentadas, 8 lámparas (6 quirúrgicas y 2 técnicas) cumplieron los criterios para realizar las pruebas de especificación completas. Las puntuaciones oscilaron entre 8 y 12 (de un total de 14), con diferencias en los ámbitos de iluminación, montaje y batería. Solo 2 lámparas proporcionaron > 35000 lux de iluminancia durante la prueba inicial, y ninguna lámpara cumplió con todas las especificaciones mínimas. De las cinco lámparas evaluadas en Etiopía, hubo una gran variabilidad en las opiniones de los cirujanos anotadas en los registros realizados, tanto sobre la calidad de la iluminación (21‐92%), como del tamaño del foco (0‐92%). En las entrevistas cualitativas surgieron comentarios importantes como la preferencia por un transporte fácil. Los cirujanos buscaban la mejor calidad al precio más razonable (dado que se utilizaban fondos propios para su adquisición) e identificaron el dispositivo menos costoso pero con alto funcionamiento como primera opción. Conclusión: El hecho de que ningún dispositivo satisfizo todas las especificaciones predeterminadas y la gran variabilidad de precios fueron los aspectos esenciales que determinaron la elección de los cirujanos. El dispositivo mejor valorado está siendo modificado por el fabricante en función de los comentarios de diseño, para lograr una lámpara quirúrgica asequible y de alta calidad diseñada específicamente para satisfacer las necesidades de entornos con recursos limitados en la mejora la seguridad quirúrgica.